Pengaruh Artificial Intelligence (AI) terhadap Willingness to Communicate pada Pembelajaran Bahasa Arab - Azizah Saad Said; Setiyawan, Agung; Saleh, Zaenal (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
The low Willingness to Communicate (WTC) in Arabic language learning has become a barrier to mastering communicative competence, often caused by students' low self-confidence. This study aims to analyze the impact of AI usage on students' WTC in Arabic language learning. A quantitative approach was employed, and data were collected using a Likert-scale questionnaire measuring WTC, self-confidence, and motivation. The sample consisted of students from Arabic Education programs at several universities, selected using cluster random sampling techniques. The findings reveal that AI has a significant positive effect on WTC by creating a supportive, interactive, and adaptive learning environment. AI provides personalized feedback that helps boost students' confidence. AI-based technology plays a crucial role in enhancing WTC and supporting the success of Arabic language learning. This study lays the foundation for developing technology-based pedagogical strategies and emphasizes the importance of improving WTC for successful Arabic language acquisition.